Judicial Practice in Applying Statutes of Limitations in Confiscation Proceedings for Illegally Acquired Property - Melkonyan, Davit; Tavadyan, Arsen (Bulletin of Yerevan University C: Jurisprudence, 2025)
This article examines the judicial practice of applying the statute of limitations in proceedings concerning the confiscation of property of illegal origin. It has become a common practice for the Prosecutor General’s Office of the Republic of Armenia to file lawsuits within the three-year period established by law and subsequently submit petitions to the court seeking to amend the subject and basis of the lawsuit. Notably, such petitions are often filed after the investigation has commenced and beyond the three-year limitation period. Nevertheless, courts consistently reject defendants' petitions to apply the statute of limitations, citing relevant provisions of the RA Civil Procedure Code.The authors argue that this interpretation of the statute of limitations contradicts specific legal provisions outlined in the RA Law "On the Confiscation of Property of Illegal Origin". Furthermore, the interpretation of Article 8 of the RA Law "On the Confiscation of Property of Illegal Origin", as well as Articles 12, 170, and 340 of the RA Civil Procedure Code, raises concerns regarding their compliance with constitutional principles and merits a thorough review.
Keywords: Statute of limitations; change of basis and subject of claim; property of illegal origin; Code of Civil Procedure